The Influence of Toponymic Elements in the Study of English Names - Mullajоnova Zukhroyulduz Alimjanovna (The Lingua Spectrum, 2026)
This article examines anthroponyms with a toponymic component as a special type of compound proper noun, formed at the intersection of anthroponymy and toponymy. The study aims to identify the structural, semantic, and linguacultural features of English anthroponyms that include a geographic element. The theoretical basis of the work consists of the works of Russian and foreign onomastic scholars devoted to the problems of proper names, toponymic nomination, and the cultural semantics of anthroponyms. This article analyzes the main models of anthroponym formation with a toponymic component and their role in reflecting territorial affiliation, migration processes, social identity, and historical memory. The study’s material includes the real names of historical and cultural figures, as well as anthroponyms from works of English literature. It is established that the toponymic component not only serves an identifying function but also carries culturally significant information, linking individual identity to geographic and historical space. The obtained results confirm the close relationship between anthroponymy and toponymy and allow us to consider anthroponyms with toponymic elements as an important element of the linguistic picture of the world.